Basic data analysis and presentation tools on the Net - González-Moreno, Luis-Millán; Peset, Fernanda (Anuario ThinkEPI, 2015)
We offer some thoughts on the need for the field of open data to evolve from the production to exploitation stage. We detail the process of generating a simple display: knowledge of sources and data extraction, local analysis or in the cloud, and using the tools needed to present the data. Information is offered on free tools readily available on the Net that an information specialist should know. Finally, knowledge acquisition in the field of data is reinterpreted, and illustrated with an example, London: the information capital, that provides advanced visualizations based on open data.